Students' feedback: An effective tool in teachers' evaluation system - Husain, Musharraf (Int J Appl Basic Med Res, 2016)
BACKGROUND: Evaluation is an integral part of medical education. Although there are various methods of teachers' evaluation, student’s feedback is considered as the most effective and reliable method albeit a controversial one. In this study, we have tried to evaluate the effectiveness of the students' feedback in teachers' evaluation in an upcoming medical college. AIM: The aim of this study was to improve the quality of teaching by introducing students' feedback as a teachers' evaluation system in a new medical college. MATERIALS AND METHODS: A feedback of second professional teachers was obtained from the fourth-semester students. This feedback was obtained through a proforma which was validated through peer review. Based on the feedback, teachers were informed about their strengths and weaknesses in a confidential manner. A uniform opportunity was then provided to these teachers for 3 months to improve their teaching skills. At the end of the period, again a questionnaire was administered to both the students and the teachers to assess the effectiveness of the feedback system. RESULTS: More than two-third of the students and teachers alike agreed that the student’s feedback is an effective tool for the faculty development. Majority of the teachers were satisfied with the present format of the feedback system and agreed that it sensitized them toward the students need. CONCLUSIONS: Student’s feedback is an effective tool for teachers' evaluation resulting in faculty development. However, other sources of feedback may also be utilized for the overall assessment of a teacher.